IMPLEMENTATION OF LEARNING DURING PANDEMIC BASED ON MAQASHID AS-SYARI'AH PERSPECTIVE - Muhammad Cholilulloh; Siti Choiriyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
This study examines the implementation of learning system during covid-19 pandemic at Pesantren of Maslakul Huda Pati based on maqashid as-syar'ah view. The aim is to find out the implementation of maqashid as-syari'ah values ??in the curriculum used and in the learning system implemented at the pesantren of Maslakul Huda Pati. The research method used was descriptive qualitative. The subjects of this study were curriculum and learning system at the pesantren. The data collected using observation, interviews, and documentation, the data then analyzed by interactive analysis with steps of data reduction, data presentation, and drawing conclusions. The results of the study showed that the values ??of maqasid as-syari'ah have been applied in the learning system during the covid-19 pandemic. It can be seen from the implementation of the value of hif? and the realization of the attitude of trust (faith), make ikhtiyar and surrender (tawakal). The value of hif? an-nafs is realized from preventive actions to minimize and break the chain of Covid-19 spread. The value of hif? al-'aql is realized from efforts to maintain learning in the pesantren even in a pandemic situation.